2016
DOI: 10.1016/j.ygcen.2015.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic–pituitary–adrenal axis activity is not elevated in a songbird (Junco hyemalis) preparing for migration

Abstract: During spring, increasing daylengths stimulate gonadal development in migratory birds. However, late-stage reproductive development is typically postponed until migration has been completed. The hypothalamic-pituitary-adrenal (HPA) axis regulates the secretion of glucocorticoids, which have been associated with pre-migratory hyperphagia and fattening. The HPA-axis is also known to suppress the hypothalamic-pituitary-gonadal (HPG) axis, suggesting the possibility that final transition into the breeding life his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 69 publications
2
10
1
Order By: Relevance
“…In fact, male residents in our study had higher expression of testis GR mRNA compared with migrants. In combination with the recent finding of increased baseline and stress-induced corticosterone plasma levels in residents compared to migrants at this time point [19,21], our findings suggest that glucocorticoid signalling could play an important role in early season breeding in juncos. Rivier & Rivest [56] suggested that CORT may bind to GR and MR to temporarily delay reproduction during stressful events.…”
Section: (B) Testicular Gene Expressionsupporting
confidence: 82%
See 1 more Smart Citation
“…In fact, male residents in our study had higher expression of testis GR mRNA compared with migrants. In combination with the recent finding of increased baseline and stress-induced corticosterone plasma levels in residents compared to migrants at this time point [19,21], our findings suggest that glucocorticoid signalling could play an important role in early season breeding in juncos. Rivier & Rivest [56] suggested that CORT may bind to GR and MR to temporarily delay reproduction during stressful events.…”
Section: (B) Testicular Gene Expressionsupporting
confidence: 82%
“…Delayed gonadal recrudescence and reproductive development could also be caused by increased activation of the endocrine stress response, as glucocorticoids are known to have suppressive effects on the HPG axis [26 -28]. However, Bauer et al [19] found that during the pre-breeding stage, resident juncos had significantly higher levels of both baseline and stress-induced corticosterone compared with migrants, thus suggesting that circulating levels of corticosterone are not suppressing reproductive development in pre-breeding juncos. However, it remains to be seen whether glucocorticoids might delay full activation of the HPG axis via increased hypothalamic and testicular sensitivity to these stress-responsive hormones (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We did not measure stress-induced corticosterone in this study, so we cannot say whether differences in stress-induced corticosterone levels might have delayed reproductive development in migrant juncos in San Diego. However, we think that is unlikely because in a similar comparison in Virginia USA, migrant juncos captured during spring had lower, not higher, levels of stress-induced corticosterone as compared with seasonally sympatric residents (Bauer et al, 2016).…”
Section: Discussionmentioning
confidence: 78%
“…Heteropatry-where closely related populations coexist during the non-breeding season (e.g., fall, winter, and /or early spring) yet pursue independent phenological and geographical trajectories during breeding-provides a unique opportunity to address the physiological mechanisms that underlie reproductive timing differences between populations (Winker, 2010;Ketterson et al, 2015;Bauer et al, 2016;Fudickar et al, 2016a,b;Greives et al, 2016;Ramenofsky et al, 2017). Broadly distributed avian species often have heteropatric distributions, in which some populations migrate while others do not (Winker, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Other avian species have been found to have elevated corticosterone prior to reproduction, regardless of migratory phenotype. This could explain the lack of difference in corticosterone levels when comparing migrant and resident Blackbirds in early spring (Romero et al 2006;Fudickar et al 2016;Bauer et al 2016b). Although, as described above, there appears to be a link between corticosterone and autumn migration in birds, the functional role of the former remains unclear.…”
Section: Neuroendocrine and Endocrine Systemsmentioning
confidence: 99%